A logistic kinetic model for isothermal and nonisothermal cure reactions of thermosetting polymers. Issue 17 (26th March 2014) - López‐Beceiro, Jorge; Fontenot, Sean A.; Gracia‐Fernández, Carlos; Artiaga, Ramón; Chartoff, Richard
ABSTRACT A model describing the low‐temperature crystallization kinetics observed for thermoplastic polymers from the melt by differential scanning calorimetry (DSC) was shown to accurately predict the cooling curves as a function of time and temperature. The model was successful for treating data for several cooling rates as well as for isothermal DSC data. In this article, we extended the model to cure reactions of thermosetting polymers. The parameters representing lower and upper exotherm reference temperatures in crystallization events have a different meaning for curing events. Thus, the model was modified to account for this change of context. The new model was tested for exothermic reactions of a Hysol® FP4527 epoxy adhesive system using data from DSC ramp heating experiments at several heating rates and also from isothermal experiments. Good fits were obtained for all the varied experimental conditions. The model made use of three fitting parameters with physical significance: a lower critical temperature (Tc) an activation energy (Eb), and a reaction order (τ + 1). Additionally, to complete the kinetic fitting, the dependence of the time to reach the reaction peak maximum for isothermal cure was considered. That dependence was found to follow a more simple model which is formally equivalent to that observed in isothermal crystallization, and which makes use of two parameters related to the limits of the temperature range in which the polymerization may occur. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40670.